Resistance Exercise Reduces Skeletal Muscle Cachexia and Improves Muscle Function in Rheumatoid Arthritis - Salaheddin Sharif; James M. Thomas; David A. Donley; Diana L. Gilleland; Daniel E. Bonner; Jean L. McCrory; W. Guyton Hornsby; Hua Zhao; Mathew W. Lively; Jo Ann A. Hornsby; Stephen E. Alway (Case Reports in Medicine)
Rheumatoid arthritis (RA) is a chronic, systemic, autoimmune, inflammatory disease associated with cachexia (reduced muscle and increased fat). Although strength-training exercise has been used in persons with RA, it is not clear if it is effective for reducing cachexia. A 46-year-old woman was studied to determine: (i) if resistance exercise could reverse cachexia by improving muscle mass, fiber cross-sectional area, and muscle function; and (2) if elevated apoptotic signaling was involved in cachexia with RA and could be reduced by resistance training. A needle biopsy was obtained from the vastus lateralis muscle of the RA subject before and after 16 weeks of resistance training. Knee extensor strength increased by 13.6% and fatigue decreased by 2.8% Muscle mass increased by 2.1%. Average muscle fiber cross-sectional area increased by 49.7%, and muscle nuclei increased slightly after strength training from 0.08 to 0.12 nuclei/μm2. In addition, there was a slight decrease (1.6%) in the number of apoptotic muscle nuclei after resistance training. This case study suggests that resistance training may be a good tool for increasing the number of nuclei per fiber area, decreasing apoptotic nuclei, and inducing fiber hypertrophy in persons with RA, thereby slowing or reversing rheumatoid cachexia.